Development of a continuous casting machine for jewelry production - E. I. Marukovich; V. A. Zemtsov; V. A. Kharkov; Yu. V. Sachenko; V. K. Deboy (Литьë и металлургия, 2000)
The article describes а continuous vertical casting machine for production of billets from precious metal for jewelry production.